Junior english revised (for pakistan) - Richards Haydn (Sunrise; Pakistan, 2007)
Junior English Book 4 by Hayden Richards is designed for secondary school students to improve their English language skills, particularly in reading, writing, and comprehension. This book provides a range of exercises, including vocabulary building, grammar practice, sentence structure, and composition. It also introduces students to literary analysis and creative writing through age-appropriate texts, helping to develop critical thinking and effective communication skills.